2013
DOI: 10.1111/jhn.12065
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition education tools used in phenylketonuria: clinician, parent and patient perspectives from three international surveys

Abstract: There was a discrepancy between clinicians and patient views regarding the perceived effectiveness of the nutrition education tools. Future research is needed surrounding the impact nutrition education may have on improved dietary compliance in patients with PKU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…This Utilization and perceived effectiveness of group clinic Fig. 3.6 Group clinic is the least utilized educational tool among international clinicians ( a ) but is perceived to be the most effective, second to one-on-one counseling ( b ) [ 8 ] data aligns with the responses from the clinicians, indicating that parents and family are an integral piece to patient learning during childhood. Patient responses also noted that printed material and handouts are the least effective tool for learning (Fig.…”
Section: Hyperphenylalaninemiamentioning
confidence: 54%
See 4 more Smart Citations
“…This Utilization and perceived effectiveness of group clinic Fig. 3.6 Group clinic is the least utilized educational tool among international clinicians ( a ) but is perceived to be the most effective, second to one-on-one counseling ( b ) [ 8 ] data aligns with the responses from the clinicians, indicating that parents and family are an integral piece to patient learning during childhood. Patient responses also noted that printed material and handouts are the least effective tool for learning (Fig.…”
Section: Hyperphenylalaninemiamentioning
confidence: 54%
“…Bernstein et al [ 8 ] also reported a discrepancy between the tools utilized in clinic and the clinician's perceived effectiveness of these tools. For example, printed materials were reported as the second most utilized educational tool, behind one-on-one counseling, yet clinicians view handouts as the least effective educational tool (Fig.…”
Section: Clinic Encounter Checklistsmentioning
confidence: 95%
See 3 more Smart Citations